Virtual Activism and Multimodal Meaning-Making: Investigating Protest Representation in Roblox through Multimodal Critical Discourse Analysis - Putri Rizki Syafrayani; Siti Aisah Ginting; Winda Setiasari (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2026)
Digital environments increasingly function as spaces where sociopolitical expression is performed through interactive media. This study explores how protest discourse and power relations are represented within a virtual protest simulation on the Roblox platform. The research applies Multimodal Critical Discourse Analysis (MCDA) by integrating Critical Discourse Analysis (Fairclough, 1995) with multimodal social semiotics (Kress & van Leeuwen, 2006, 2021). Data were obtained from five scenes collected through close-playing observation of a Roblox protest simulation associated with the “Free Palestine” movement. The analysis focuses on the interaction of linguistic, visual, gestural, spatial, and auditory semiotic resources embedded within the virtual environment. The findings reveal that protest representation in the simulation emerges through the coordinated use of symbolic imagery, avatar interaction, spatial positioning, and textual expressions. These multimodal configurations communicate meanings related to solidarity, institutional authority, embodied resistance, and humanitarian advocacy. The study demonstrates that gaming platforms such as Roblox can function as discursive arenas where ideological positions and political narratives are negotiated through interactive communication. By extending Multimodal Critical Discourse Analysis into participatory gaming environments, this research contributes to the understanding of digital protest discourse in contemporary media cultures.